IMPLEMENTASI METODE HAVERSINE FORMULA PADA SISTEM INFORMASI GEOGRAFIS RUMAH KOST DAERAH TANGERANG SELATAN - endah budiyanti (LIAISON JOURNAL OF BEST, 2022)
The development of information technology makes people's behavior in all activities that are usually carried out by individuals or an institution. People now really need the help of devices in digital form, this dependence is due to increasingly complex aspects of life. This aspect of life requires that all activities be carried out quickly and effectively and efficiently. One of the needs for the community is a place to live, especially for migrants in a place such as local people who study in urban areas. As well as new students from the area definitely need a place to stay during their time studying at a university. Gunadarma University is one of the campuses that has students who come from all regions of Indonesia and some from abroad. The need for residential information can be assisted by the Geographic Information System in this research using the haversine formula method. Prospective new students can easily find a place to live or boarding according to their needs. This information system also helps boarding house owners to widely inform their boarding house rental business. This study applies a qualitative descriptive model, namely data analysis based on the results of interviews, observations and field surveys. The information system in this study was designed with the PHP and MySQL programming languages. The research succeeded in producing a geographic information system by displaying the location of the boarding house in the form of a map provided by the Google Company. Keyword: Geographic Information System for Boarding Places, haversine formula, Depok City